From Gratitude to Mental Health: Action Research Gratitude Journaling - Layyinah, Hazimatul; Akbar, Zarina; Suryaratri, Ratna Dyah (Jurnal Indonesia Sosial Sains, 2026)
Academic stress is one of the psychological challenges commonly faced by boarding school students due to high academic demands and limited social interaction. This study aimed to examine the effectiveness of gratitude journaling in reducing academic stress among eleventh-grade students at Al Nahdlah Islamic Boarding School, Depok. Using the Kemmis and McTaggart (1988) action research model, the study was conducted through three cycles consisting of planning, acting, observing, and reflecting stages. Data were collected using the Academic Stress Scale (QASSE), observation, gratitude journals, and semi-structured interviews. Quantitative data were analyzed using paired-sample t-tests, while qualitative data were analyzed thematically. The results showed a significant reduction in academic stress in Cycle I (p < 0.05; Cohen’s d = 1.214, large effect) and Cycle III (p = 0.037; Cohen’s d = 0.649, moderate effect). Qualitative findings revealed improvements in students’ emotional awareness, reflection, and gratitude expression. These results indicate that gratitude journaling can serve as an effective psychoeducational strategy for reducing academic stress and promoting emotional well-being in boarding school students.